ANALISIS PERILAKU NASABAH TERHADAP MINAT BERINVESTASI DEPOSITO - Ramadhan, Anugrah Harry; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to test the influence of attitude, subjective norm and behavior control to the investment interest, as well as the influence of investment interest to the deposit investment. The purposive sampling method is used to determine the samples to 120 bank customers who own deposit are selected as the respondents, and the primary data uses the Theory of Planned Behaviors instrument (Ajzen, 1991). The result of the research has been conducted by using the Structural Equation Modeling-Partial Least Square (SEM-PLS) with the SmartPLS program version 3.2 shows that the investment interest is significantly influenced by attitude and behavior control whereas the subjective norm does not have any significant influence. The following finding shows that the deposit investment is significantly influenced by the investment interest. The influence to the investment interest is determined by the value of RÂ² is 0.543, which means that the investment interest is 54.30%, it is influenced by attitude, subjective norm, and behavior control, whereas the remaining is 45.70%, it is influenced by other models outside of the research. The value of RÂ² for the deposit investment is 0.763 which means that the deposit investment is 76.30%, it is influenced by investment interest, whereas the remaining is 23.70%, it is influenced by other variables outside the model.Keywords: attitude, subjective norm, behavior control, investment interest, deposits interest